Trace metals concentration in water hyacinth implicates the saltwater barrage altered hydrography of Kochi backwaters, southwest Coast of India. (July 2021) - Arunpandi, N.; Jyothibabu, R.; Savitha, M.K.M.; Parthasarathi, S.; Rashid, C.P.; Josna, M.P.; Santhikrishnan, S.; Sarath, S.; Balachandran, K.K.
Abstract: This study in the Kochi backwaters (KBW) presents the distribution of 9 trace metals (Fe, Zn, Cu, Mn, Ni, Co, Cr, Cd, Pb) in different parts (root, stolon and leaf) of the common water hyacinth Eichhornia crassipes during three different seasons [Pre-Monsoon (PRM), Southwest Monsoon (SWM), and Northeast Monsoon (NEM)]. The hyacinth was collected from 4 sections upstream of the KBW where a saltwater barrage [Thannermukkom Barrage (TB)] prevents saltwater intrusion. Results showed that regardless of seasons, all the trace metals concentration in different parts of Eichhornia varied in the following order: roots > stolon > leaves. All the trace metals except Fe showed their highest concentration during the PRM when TB introduces stagnancy of the water upstream through flow restrictions. Instead, Fe was high during the SWM associated with increased river influx at that time. Overall results showed that the hydrographical alterations of TB upstream of KBW have clear imprints on the trace metals concentrated in the hyacinth Eichhornia crassipes . Highlights: Trace metals in water hyacinth was assessed in the Kochi backwaters Roots concentrated maximum trace metals followed by stolon Trace metals in the water hyacinth were the highest during Pre-Monsoon Water stagnancy was the main reason for high trace metals values during the PRM